2012
DOI: 10.1002/mc.21904
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FOXJ1 in hepatocellular carcinoma: Correlation with patients' prognosis and tumor cell proliferation

Abstract: FOXJ1 is a member of the forkhead box (FOX) family of transcription factors. Recent studies suggested that FOXJ1 may function as a tumor suppressor gene in breast cancer. To investigate the potential roles of FOXJ1 in hepatocellular carcinoma (HCC), expression of FOXJ1 was first examined in eight paired frozen HCC and adjacent noncancerous liver tissues by Western blot, and we found that FOXJ1 was upregulated in HCC specimens. In addition, immunohistochemistry was performed to confirm our results in 108 HCC sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…For example, a recent study indicated that FOXJ1 expression was increased and associated with aggressive characteristics in hepatocellular carcinoma. Thus, FOXJ1 was proposed as a prognostic marker in patients with hepatocellular carcinoma (40). By contrast, a previous study proposed that FOXJ1 was decreased and may function as a tumor suppressor gene in breast cancer (39).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, a recent study indicated that FOXJ1 expression was increased and associated with aggressive characteristics in hepatocellular carcinoma. Thus, FOXJ1 was proposed as a prognostic marker in patients with hepatocellular carcinoma (40). By contrast, a previous study proposed that FOXJ1 was decreased and may function as a tumor suppressor gene in breast cancer (39).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, overexpression of FOXJ1 appears to be involved in proliferation and cell-cycle progression. In brief, little is known regarding the potential roles of FOXJ1 in carcinogenesis (40). The expression of FOXJ1 and its function in human RCC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…HCC is the fifth most common malignant tumor worldwide, with an incidence of approximately 626,000 cases each year [1,2]. In China and Southeast Asia, HCC is highly associated with viral hepatitis B and cirrhosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…FOXJ1 is over-expressed in HCC. It is associated with histological grade, poor prognosis and with tumour cell proliferation [19]. Hedgehog signalling pathway mediates invasion and metastasis of HCC via ERK pathway.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…IHC is mandatory for the diagnostics of haematological neoplasms and epithelioid haemangioendothelioma. Assessment of tumour biological potential can be done by IHC, evaluating Ki-67, Cyclin D1, FOXJ1, stem cell markers, matrix metalloproteinases and other markers [7][8][18][19][20][21][22]. Novel markers appear continuously as heat-shock protein 70 [23].…”
mentioning
confidence: 99%